1994
DOI: 10.1126/science.8122111
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ras-Induced Transformation of NIH 3T3 Cells by Activated Gα S

Abstract: Conversion of external signals into proliferative responses may be mediated by interactions between signaling pathways that control cell proliferation. Interactions between G alpha s, the alpha subunit of the heterotrimeric guanine nucleotide binding protein that stimulates adenylyl cyclase, and Ras, an important element in growth factor signaling, were studied. Expression of activated G alpha s in NIH 3T3 cells increased intracellular concentrations of adenosine 3',5'-monophosphate (cAMP) and inhibited H-Ras-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 22 publications
4
74
1
Order By: Relevance
“…1C). Interestingly, this kinetic profile contrasts with our previous observations in NIH 3T3 cells (16), where cAMP and Rap1b negatively modulate cell growth (38)(39)(40). In these cells, cAMP stimulation of Rap1b shows an initial peak similar to the one described here for thyroid cells, followed by a second wave of sustained activation (16,39).…”
Section: A Physiological Model To Test the Notion That Rap1b Mediatescontrasting
confidence: 54%
“…1C). Interestingly, this kinetic profile contrasts with our previous observations in NIH 3T3 cells (16), where cAMP and Rap1b negatively modulate cell growth (38)(39)(40). In these cells, cAMP stimulation of Rap1b shows an initial peak similar to the one described here for thyroid cells, followed by a second wave of sustained activation (16,39).…”
Section: A Physiological Model To Test the Notion That Rap1b Mediatescontrasting
confidence: 54%
“…We have recently reported that growth of cells, NIH 3T3, normally inhibited by cAMP (Magnaldo et al, 1989;Chen and Iyengar 1994), can be potently stimulated by cAMP if the PKA subunit RIIb is expressed in these cells (Porcellini et al, 2003). The presence of RIIb in these lines amplified cAMP survival and transcriptional signals.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which v-Abl activates Ras remains unknown, it has been suggested that v-Abl can interact directly with Shc thereby initiating the formation of a complex with Grb2-mSos and ensuing Ras-Raf activation (49). A mutationally activated form of Ras, most commonly G12V, is found in up to 30% of all human tumors (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Caveolin-1 Expression Inhibits Ras-mediated Transcriptional mentioning
confidence: 99%